IMPACT OF OPIOID DEPRESCRIBING AND TAPERING ON MENTAL HEALTH AND SOCIAL FUNCTIONING IN PATIENTS WITH CHRONIC NON – CANCER PAIN: AN OVERVIEW OF CURRENT EVIDENCE - Mateusz Wnęk; Michał Adam Łebek; Wiktoria Zofia Komornik; Jakub Jan Piec; Damian Grębosz; Wojciech Kukiełka; Bartłomiej Andrzej Sałapski; Dominika Weronika Brożyna; Jarosław Dudek; Jakub Dawid Gałwiaczek (International Journal of Innovative Technologies in Social Science, 2026)
Background. Long-term opioid therapy for chronic non-cancer pain is associated with numerous adverse effects, including psychological distress, dependence, and impaired functioning. In response to growing concerns about opioid-related harms, opioid deprescribing and tapering strategies have gained increasing attention in clinical practice. However, their impact on patients’ mental health and social functioning remains incompletely understood. Aim. This review aimed to evaluate the available evidence on the effects of opioid deprescribing and tapering on mental health and social functioning in patients with chronic non-cancer pain. Material and methods. A literature review was conducted using major biomedical databases, including PubMed, MEDLINE, Scopus, Web of Science, and the Cochrane Library. Eligible studies included peer-reviewed articles examining opioid deprescribing or tapering in adults with chronic non-cancer pain and reporting outcomes related to mental health, social functioning, or patient-reported functioning Results. The available evidence suggests that patients undergoing opioid deprescribing frequently present with substantial psychological distress, including depression, anxiety, and pain catastrophizing. Mental health outcomes during tapering are heterogeneous and influenced by the pace of dose reduction, patient involvement in decision making, and access to psychological support. Qualitative studies commonly highlight social factors: stigma, communication with healthcare providers, and availability of alternative pain management strategies. Conclusions. Opioid deprescribing in patients with chronic non-cancer pain represents a complex clinical process with potential implications for both mental health and social functioning. Individualized tapering strategies, patient involvement in treatment decisions, and adequate psychological and multidisciplinary support appear essential for minimizing adverse outcomes and improving patient experiences during opioid dose reduction.